Automatic Gas Control System In The Motorcycle Braking Process With The Concept Of Non-Uniform Slowing Down Motion - Anang Suryana; Anggy Pradiftha Junfithrana; Ilman Himawan Kusumah; Aryo De Wibowo; Edwinanto; Marina Artiyasa; Yufriana Imamulhak; Yudha Putra (Universitas Nusa Putra, 2020)
When motorcyclists have an accident, they are at high risk of suffering severe or fatal injuries. The difficulty experienced by motorcyclists and considered one of the most complicated to do in an emergency is braking because motorcycle accidents are often caused by loss of control or stability when braking as evasive action. In the braking process, a motorcycle must pay attention to distance and speed so that the deceleration during braking is by the kinematic concept to avoid the shock force during braking, in this study uses research and development methods in making automatic braking systems on motorbikes. The actuator system controls the brake pedal, and the gas pedal uses a stepper motor. The two stepper motors will move automatically if the motorbike detects an object in front of it at less than 4 meters. The angle of the stepper motor that drives the brake lever is in a span between 0 degrees to 30 degrees, while the tip of motion of the stepper motor that moves the gas pedal is in a span of 0 degrees to 70 degrees. The angle movement of the stepper motor is influenced by the distance detected by the HC-SR04 type proximity sensor and the motorbike speed detected by the KY-003 type speed sensor, which works by utilizing the hall effect principle. The results of the tests that have been carried out show that the automatic braking system created can work well with an indicator that there is no shock force during the automatic braking process